Impact of oocyte donation on obstetric and perinatal complications in twin pregnancies. (2nd June 2020) - Boria, Felix; de la Calle, Maria; Cuerva, Marcos; Sainz, Angela; Bartha, Jose Luis
Abstract: Aim: To evaluate obstetric and perinatal outcomes of twin pregnancies obtained after in vitro fertilization with donated oocytes. Methods: This is a case-control study comparing 50 women with twin pregnancies after oocyte donation (OD) and 50 women after in vitro fertilization with autologous oocytes. Clinical records were reviewed and obstetric and perinatal outcome variables including rates of preeclampsia, gestational diabetes, pregnancy-induced hypertension, preterm delivery, premature rupture of membranes, cesarean delivery, birth weight, Apgar score, pH test were compared. Results: Women in the OD group were significantly older than those in the AO group (mean 40.8 versus 36 years old, p < .001). There were a higher risk of preeclampsia (OD 24% versus AO 8%), cesarean delivery (OD 90% versus AO 66%), and preterm birth before 37 weeks (OD 52% versus AO 32%). After adjustment for maternal age, only the risk of preterm birth remained significantly higher (OR 3.2 (1.15–8.86); p = .025). Comparing neonatal outcomes, there were no differences in birth weight, pH or Apgar score at birth. Conclusions: Twin pregnancies after OD are associated with a higher risk of preterm birth before 37 weeks of gestation. However, this did not translate into increased rate of adverse perinatal outcomes.